Unia Europejska w dążeniu do przestrzegania praw człowieka na Białorusi - Kakarenko, Ksenia (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
Belarus is not a member state of the European Union, nevertheless the European Parliament is clearly interested in the observation of human rights in that country. An analysis of the legal norms contained in the Constitution of the Republic of Belarus shows that all the important rights and freedoms that form a part of European standards of human rights are contained within it. Nevertheless, this Constitution has a merely ‘semantic’ character. There are no actual guarantees given in specific statutes. The norms contained in statutes enable the public authorities to violate any constitutional norms. What is more, these powers are also provided by statutory acts. This article presents what sanctions have issued from the European Union in response to human rights violations in Belarus over the last 20 years.
European Union endeavors for human rights to be respected in Belarus